Wawasan Alquran Tentang Pendidikan - Saiful Bahri (At-Tafkir, 2020)
The Term Tarbiyah (education) that in the Quran has given deep insights into various problems, one concerning education, insights that human beings should exhume explicitly, especially in terms of the educational term, then in this case there are some verses that the author presents about the word Tarbiyah, among them the tarbiyah word in Q.S. Al Isra:24, mentioned by the word Rabbayani, in Q.S Al Rum:39, described by the word Yarbu, in Q.S Ali Imran:79, the word Rabbani and Q.S Asy Syu’ara:18 explain that the word Nurabbika”